Supplemental Effect of Creatine and Carnitine with theirCombination on some productive traits of broiler chickens. - H.Al-Shemmari, Wala'a; A.Fahad, Majeed (Journal of Kerbala for Agricultural Sciences, 2017)
The research was conducted to investigate the effect of supplementation of Creatine and Carnitine with their combination on some productive traits of Ross 308 broiler chicks. Atotal number of 450, one old chicks were used in the research , those chicks were randomly alloted in to 9 equal treatments and each treatment included 2 equal replicates.Chicks were fed on diets supplemented with Creatine and Carnintine. treatments were arranged as follow: The 1st treatment fed on an ordinary diet with out any supplement where as the 2nd and 3rd treatments fed on a diet supplemented with 100 and 200 mg/kg Creatine respectively. The 4th and 5th treatments fed diets supplemented with 100 and 200 mg/kg Carnintine respectively. The 6th treatment supplemented with 100 mg / kg Creatine plus 100 mg / kg Carnintine , mean while the 7th treatment supplemented with 200 mg / kg Creatine plus 200 mg/kg Carnintine. The 8th treatment supplemented with 100 mg / kg Creatine plus 200 mg / kg Carnintine and the 9th treatment supplemented with 200 mg / kg Creatine plus 100 mg / kg Carnintine. Chicks in the experimental treatments fed adlibitum on the starter diet till 21 day , then transferred to the growing diet till 42 day. Results illustrated surpassing of live body weights , weight gains as well as improvement of feed conversion ratio with reduction of the utilized feed of broiler chickens that fed diets supplemented with Creatine and Carnintine